2010
DOI: 10.1158/1078-0432.ccr-10-0802
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Everolimus (RAD001) in Previously Treated Small Cell Lung Cancer

Abstract: Purpose: Mammalian target of rapamycin (mTOR) is a promising target in small cell lung cancer (SCLC). We designed a phase II study of everolimus, an mTOR inhibitor, in previously treated, relapsed SCLC. Experimental Design: Patients were treated with everolimus 10 mg orally daily until disease progression. The primary endpoint was disease control rate (DCR) at 6 weeks. PI3K/Akt signaling pathway biomarkers were evaluated on baseline tumor tissue. Results: A total of 40 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(66 citation statements)
references
References 33 publications
1
65
0
Order By: Relevance
“…Twenty trials reported pneumonitis events, eight trials reported cough, and twelve trials reported dyspnea. Sixteen trials (seven temsirolimus, eight everolimus, and one ridaforolimus) were single arm studies or randomized patients to different doses/schedules of an mTOR inhibitor (Table 2) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Six trials (one temsirolimus, four everolimus, and one ridaforolimus) randomized patients to an mTOR inhibitor arm or a non-mTOR inhibitor control arm (Table 3) [22-27].…”
Section: Search Resultsmentioning
confidence: 99%
“…Twenty trials reported pneumonitis events, eight trials reported cough, and twelve trials reported dyspnea. Sixteen trials (seven temsirolimus, eight everolimus, and one ridaforolimus) were single arm studies or randomized patients to different doses/schedules of an mTOR inhibitor (Table 2) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Six trials (one temsirolimus, four everolimus, and one ridaforolimus) randomized patients to an mTOR inhibitor arm or a non-mTOR inhibitor control arm (Table 3) [22-27].…”
Section: Search Resultsmentioning
confidence: 99%
“…The inhibition of individual components of the pathway leads to a potent induction of apoptosis and reversion of chemoresistance in preclinical studies (Razzini et al 2000;Wu et al 2005). In clinical trials, however, single agent administration of mTOR inhibitors exerted only limited antitumor activity (Tarhini et al 2010). Combination therapies using more potent dual PI3K/mTOR inhibitors that circumvent the reactivation of the PI3K pathway through a negative feedback loop may possibly be more effective (Sun et al 2005).…”
Section: Therapeutic Targetsmentioning
confidence: 99%
“…Thus, the Akt/mTOR signaling pathway became an especially promising target for cancer therapy (Yuan et al, 2009). The mTOR inhibitor rapamycin and its analogues, such as temsirolimus (CCI-779), everolimus (RAD001), and ridaforolimus (AP23573), have been tested extensively in clinical trials for the past few years and have shown preliminary promise of efficacy in several tumor types, including NSCLC (Price et al, 2010;Tarhini et al, 2010;Witzig et al, 2011). However, the single-agent use of mTOR inhibitors for cancer therapy did not meet expectations (Dowling et al, 2009), while combination of an mTOR inhibitor with other anticancer agents was shown a better therapeutic efficacy in several clinical trials.…”
Section: Introductionmentioning
confidence: 99%